II Global Trends in Tertiary Education QA : Challenges and Opportunities in Internal and External QA - Susanna Karakhanyan; Kevin Kinser (Brill, 2025)
Is tertiary education well-equipped to embrace changing paradigms and modes of learning? Are quality assurance measures actually designed to support higher learning for diverse students in diverse settings? By building on a legacy of nearly two decades, Global Trends attempts to address efficiency, relevance, and transformative power of quality assurance and accreditation measures by looking into the developmental trends of both internal and external quality assurance and related challenges across the globe. Providing an international review across seven regions – Africa, Arab States, Asia-Pacific, Eastern Europe, Latin America and Caribbean, North America and Western Europe – the study is a joint effort of QA and TE networks under the umbrella of INQAAHE. A globally diverse set of authors present and preserve our QA legacy by shaping a tradition of a comprehensive historical coverage of QA trends, learning from the past to inform sustainable futures. Contributors are: Hazman Shah Abdullah, Magda Abou El Safa, Rabie'e Al-Rashdi, Renato Bartet, T. Chan Basaruddin, Baghdad Benstaali, Asiyah Bukhari, Sean Manley Casimir, Ying Chen, Michelle Claville, Sylvia Demas, Vesna Dodikovic-Jurkovic, Arianna Fang Yu Lin, Sofía Farizano, Eva Fernandez De Labastida, Fernando Leon Garcia, Anna Gover, Ariadna Guaglianone, Christopher Hong-Yi Tao, Edward Hung Cheng Su, Ngepathimo Kadhila, Susanna Karakhanyan, Maria Kelo, Kevin Kinser, Simona Lache, Peter Levente Lakatos, Mary Catharine Lennon, Leah Matthews, Francesc Pedro, Anna Prades, Martín Strah, Wondwosen Tamrat, Helmuth Trefftz, Aurelija Valeikiene, Joseph Vibert, Ariana De Vincenzi, Angela Yung Chi Hou, Jianxin Zhang, Kyle Ziwei Zhou.